(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In article the structural-semantic features of the military vocabulary in Ukrainian language are researched. The models of morphological, lexical-semantic and analytical derivation are described.